The (Israeli) attacks on southern Lebanon between (1948-1973) - Ibrahim Muhammad Jabbar ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Lebanon entered an important stage in its history following its participation on the side of the Arab countries, in the first Arab war against (Israel) in 1948, which resultedin the arrival of Palestinian refugee convoys to southern Lebanon, and thus the Palestinian presence began in southern Lebanon. The June 1967 war also led to a political and economic setback for the Arab countries, and its repercussions were a new territorial loss in favor of the (Israeli) occupation, and consequently the displacement of thousands of Palestinian citizens towards Syria, Lebanon and Jordan. The (Israeli) attacks on the south took on a very ferocious size, so the various areas of southern Lebanon became the target of continuous raids and bombardments, and in the October 1973 war, southern Lebanon was not surrendered again